Gambaran Tingkat Stress Perawat Pelaksana dalam Melakukan Intervensi Keperawatan pada Masa Pandemi Covid-19 di Rumah Sakit Jiwa Daerah Provinsi Jambi - Suri, Marta; Putri, Vevi Suryenti (Universitas Baiturrahim, 2021)
The number of deaths due to Covid-19 cases in Indonesia continues to increase. All nurses involved in the care of Covid-19 patients have sacrificed their personal and family interests. Nurses have sacrificed safety and the threat of contracting a virus that can end in death. This high burden and worry will certainly increase the nurse's stress level from mild to severe. This condition can also occur even after 1 year of the pandemic has passed, so it can be concluded that it can be acute or chronic. This type of research is descriptive analytic with a population of 130 nurses, a sample of 40 respondents. The results of this study indicate that 75.5% of nurses experience moderate stress, for this reason it is necessary to tighten the standard additional empirical preventive measures for patient cases under surveillance and confirmation of COVID-19 and overall infection control prevention in carrying out nursing interventions by nursing management in hospitals